(untitled) (Eurasian Journal of Ecology, 2016)
This article demonstrates the dependence of the specializations of regions on their ecological situations and related national regulative measures are examined as environmental control costs per caput in every region. Furthermore, the detailed analysis of the structure of Kazakhstan energetic complex by three energetic zones is given. The actuality to develop alternative energy or renewable energy resources on the territory of Kazakhstan is proved by many factors studied within the present article, complies with the principles of «green» economy and is included in the ustainable development strategy of our Republic as well.